(untitled) (TEL Tempo, Espaço e Linguagem, 2020)
We aim to identify and analyze the history of the Obelisk, established in Eleutério Galdino de Andrade Square, in Peabiru, Paraná, in order to understand the values expressed by it in its founding and in the present time, in the perception of the residents of the municipality. The monument is a concrete monolith with a quadrangular base that stretches and tapers until it forms a pyramid at its top, and has five bronze plates with tributes to the founding pioneers of the municipality and records of historical dates. The methodological procedures used in this research involved interviews with historians, geographers and longtime Peabiru residents, questionnaires with 157 Olavo Bilac State School students, between 14 and 17 years of age, and reading of news published by the main journalistic media of the region. Through the gathered data it was possible to observe the use of the Obelisk, in its founding, as a means of perpetuating the power and memory of its creators, being today seen as an identity symbol of Peabiru society. However, the new generation does not feel this connection with the monument, perhaps due to its absence, due to age, in the main events registered in the memory of the older inhabitants. Thus, we observe the need to problematize and rework the history of the so that it does not exclude certain groups for others, and to disseminate the results among the youth, relating them to their experiences, so that these young people to develop a better understanding of the importance of the Obelisk for Peabiru.